(untitled) (International Journal of Medical and Surgical Sciences, 2015)
Oral Mucosal Melanoma is a very aggressive disease that requires early detection by biopsy suspicious lesions, characteristics and surgical treatment resection with wide margins, cervical lymph node dissection and adjuvant therapies aimed at eradicating systemically neoplastic cells. The aim of this report is to show the evolution of this disease in a case where the patient did not accept treatment and thus understanding its earlier stage, the subsequent invasion of adjacent tissues and finally as it spread to the cervical lymph nodes and vital organs remote triggering systemic failure.